Assessment of selenium spatial distribution using μ-XFR in cowpea (Vigna unguiculata (L.) Walp.) plants: Integration of physiological and biochemical responses - Lanza, Maria Gabriela Dantas Bereta [UNESP]; Silva, Vinícius Martins [UNESP]; Montanha, Gabriel Sgarbiero; Lavres, José; Pereira de Carvalho, Hudson Wallace; Reis, André Rodrigues dos [UNESP] (Elsevier, 2021)
Low concentrations of selenium (Se) are beneficial for plant growth. Foliar Se application at high concentrations is toxic to plants due to the formation of reactive oxygen species (ROS). This study characterized Se toxicity symptoms using X-ray fluorescence (XRF) technique in response to foliar Se application in cowpea plants. Five Se concentrations (0, 10, 25, 50, 100 e 150 g ha−1) were sprayed on leaves as sodium selenate. The visual symptoms of Se toxicity in cowpea leaves were separated into two stages: I) necrotic points with an irregular distribution and internerval chlorosis at the leaf limb border (50–100 g ha−1); II) total chlorosis with the formation of dark brown necrotic lesions (150 g ha−1). Foliar Se application at 50 g ha−1 increased photosynthetic pigments and yield. Ultrastructural analyses showed that Se foliar application above 50 g ha−1 disarranged the upper epidermis of cowpea leaves. Furthermore, Se application above 100 g ha−1 significantly increased the hydrogen peroxide concentration and lipid peroxidation inducing necrotic leaf lesions. Mapping of the elements in leaves using the XRF revealed high Se intensity, specifically in leaf necrotic lesions accompanied by calcium (Ca) as a possible attenuating mechanism of plant stress. The distribution of Se intensities in the seeds was homogeneous, without specific accumulation sites. Phosphorus (P) and sulfur (S) were found primarily located in the embryonic region. Understanding the factors involved in Se accumulation and its interaction with Ca support new preventive measurement technologies to prevent Se toxicity in plants.
Keywords: Agronomic biofortification; Antioxidant metabolism; Scanning electron microscopy; Selenium; Vigna unguiculata; X-ray fluorescence microscopy